2005
DOI: 10.1128/jcm.43.6.2991-2993.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of a Semiautomated, Standardized Assay for Detection of Hepatitis B Virus DNA in Blood Donations

Abstract: We evaluated the COBAS Ampliscreen hepatitis B virus (HBV) test using standards, seroconversion panels, consecutive donations, and samples from patients with abnormal alanine aminotransferase and chronic hepatitis C. Specificity was 100% and sensitivity was 20 IU/ml. In seroconversion panels, HBV DNA was detected up to 4 to 18 days before HBsAg, suggesting that this assay is useful in shortening the infectious window phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The acute hepatitis B virus (HBV) infection window period extends from 37 to 87 days (mean, 59 days) 1 after acquisition of the virus. Both HBV surface antigen (HBsAg) and total antibody to HBV core antigen (anti‐HBc) test negative during this period; however, the HBV genome can be detected in plasma by molecular tests as shown by seroconversion panel testing 2 . Blood units donated during the early acute infection period are not identified by current mandatory testing; nevertheless, blood products obtained from these units might transmit HBV to transfusion recipients.…”
mentioning
confidence: 99%
“…The acute hepatitis B virus (HBV) infection window period extends from 37 to 87 days (mean, 59 days) 1 after acquisition of the virus. Both HBV surface antigen (HBsAg) and total antibody to HBV core antigen (anti‐HBc) test negative during this period; however, the HBV genome can be detected in plasma by molecular tests as shown by seroconversion panel testing 2 . Blood units donated during the early acute infection period are not identified by current mandatory testing; nevertheless, blood products obtained from these units might transmit HBV to transfusion recipients.…”
mentioning
confidence: 99%
“…It is considered to be a superior technique for the early detection of HBV infection 24,25,28 . However, despite the regular use of minipool NAT for blood donor screening, the risk of posttransfusion HBV infection persists 20‐25 . In this study, we developed an unprecedented high‐sensitivity HBsAg detection prototype and investigated whether such an assay could reduce the risk of undesired HBV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that many countries perform HBV DNA and HBsAg screening tests, posttransfusion HBV infection continues to occur 20‐25 . This is because a relatively long infectious window period remains before HBV DNA and HBsAg become detectable in serum 19‐22,24‐30 1,26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…173 NAT assay were reactive 10-20 days before HBsAg. 169,174 No studies reported turnaround time for conducting the test.…”
Section: Hbv Natmentioning
confidence: 99%